1996
DOI: 10.1136/jnnp.61.4.339
|View full text |Cite
|
Sign up to set email alerts
|

The role of laboratory investigation in the diagnosis and management of patients with suspected herpes simplex encephalitis: a consensus report. The EU Concerted Action on Virus Meningitis and Encephalitis.

Abstract: As effective therapies for the treatment of herpes simplex encephalitis (HSE) have become available, the virology laboratory has acquired a role of primary importance in the early diagnosis and clinical management of this condition. Several studies have shown that the polymerase chain reaction (PCR) of CSF for the detection of herpes simplex virus type 1 (HSV-1) or type 2 (HSV-2) DNA provides a reliable method for determx ining an aetiological diagnosis of HSE. The use of PCR in combination with the detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
7

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(108 citation statements)
references
References 85 publications
2
99
0
7
Order By: Relevance
“…Though the initial studies provided aciclovir for 10 days, relapses beyond this were subsequently reported [123,124], prompting most physicians to provide a longer duration of therapy (notably, many cases of apparent relapse may be immune mediated rather than infectious-see below). Some advocate repeat CSF PCR at 14-21 days, with longer treatment if PCR is positive [125,126], though we generally reserve this for patients who have had a complicated course or have not responded to therapy as well as expected. A recently completed trial noted a lack of benefit from an additional 3 months of oral valaciclovir for the reduction of post-HSVE neuropsychiatric complications in 87 adults with PCR-proven HSVE [127].…”
Section: Duration Of Treatmentmentioning
confidence: 99%
“…Though the initial studies provided aciclovir for 10 days, relapses beyond this were subsequently reported [123,124], prompting most physicians to provide a longer duration of therapy (notably, many cases of apparent relapse may be immune mediated rather than infectious-see below). Some advocate repeat CSF PCR at 14-21 days, with longer treatment if PCR is positive [125,126], though we generally reserve this for patients who have had a complicated course or have not responded to therapy as well as expected. A recently completed trial noted a lack of benefit from an additional 3 months of oral valaciclovir for the reduction of post-HSVE neuropsychiatric complications in 87 adults with PCR-proven HSVE [127].…”
Section: Duration Of Treatmentmentioning
confidence: 99%
“…Detection of HSV DNA in the CSF by PCR remains the mainstay for the diagnosis of HSV encephalitis, 38 although results of this laboratory test may be false negative or may arrive belatedly. Thus, results of imaging studies are important to decide whether antiviral treatment has to be started in patients with suspected HSV encephalitis.…”
Section: Viral Meningoencephalitismentioning
confidence: 99%
“…The sensitivity of the PCR reaction depends on a series of factors. The sensitivity of PCR for HSV is 94%, the specificity is 98%, positive predictive value is 95% and negative predictive value is 98% [33,38,[44][45][46][47][48].…”
Section: Lymphocytic Meningitis With Infectious Etiology Viral Meningmentioning
confidence: 99%